Improving Maternal Health Literacy in Kansas: Curriculum Adaptation of Becoming a Mom Through a Public Health and Equity Lens - Jonak, Carissa (My University, 2025)
This Integrated Learning Experience report describes a graduate internship conducted at the Kansas Department of Health and Environment, specifically within the Bureau of Family Health. The focus of the internship was the adaptation of the Becoming a Mom prenatal education curriculum to improve health literacy, cultural responsiveness, and accessibility for diverse and historically underserved populations in Kansas. The project aimed to address persistent maternal and infant health disparities by ensuring that prenatal education materials are written at or below a sixth-grade reading level, follow plain language principles, and incorporate inclusive images and content that reflect the lived experiences of pregnant individuals across the state. Key activities included reviewing and revising curriculum content, applying evidence-based communication strategies, and integrating stakeholder feedback gathered through Health Equity Opportunity Project workgroup meetings and collaborative partnerships. The project also involved supporting grant-related documentation, attending Title V MCH and Kansas Perinatal Community Collaborative meetings, and preparing the curriculum for field testing. As part of this process, the intern developed a style guide, revision tracking system, and recommendations for future updates to supporting materials, including the slide deck used in live and virtual BaM sessions. This work contributed to the Kansas Department of Health and Environment’s mission to improve perinatal health outcomes through equitable and community-centered interventions. While reviewing and drafting updates to the Becoming a Mom curriculum, principles of reproductive justice, intersectionality, and inclusive representation in health education were applied to ensure the content reflected participants' diverse identities and experiences. By revising the Becoming a Mom curriculum to use plain language, reduce medical jargon, and include diverse imagery and culturally affirming content, the project actively challenged assumptions about who maternal health education is for and how it should be delivered. These changes were designed to better serve participants across lines of race, language, socioeconomic status, and education—core concerns that acknowledge how intersecting identities affect access to care. Field testing and further review of accompanying teaching tools will inform continued improvements. This project represents a practical application of public health and principles of reproductive justice, intersectionality, and inclusive representation in action, supporting better maternal health outcomes and a more just, inclusive model of prenatal care.
Keywords: Maternal health; Prenatal education; Health literacy; Reporductive justice; Curriculum development; Public health communication